Digital Transformation of Small Business in the Most Fragile and Marginalized Segments of the Economy (aSSIST Business Review, 2026)
Digital transformation extends beyond merely adopting technology; it encompasses structural changes and innovations across business operations, accelerating decision-making processes. This study was conducted to support small business owners at the economic grassroots in enhancing their competitiveness and adapting effectively to the rapidly changing market environment through data-driven decision-making. Small business owners often face significant constraints in digital transformation due to limited capital, workforce, and knowledge. The key obstacles hindering digital transformation include low awareness of digital technologies, absence of skilled personnel, and lack of financial resources. To address these issues, this study proposes a four-step approach: data collection, storage, analysis, and improvement, and presents a practical model for implementing digital transformation centered around cost-effective digital tools and actionable strategies. Digital transformation can increase market responsiveness, maximize efficiency, and create long-term growth opportunities for small business owners. This research underscores that a tailored approach considering the practical constraints of small business owners and a phased implementation plan can lower the barriers to digital transformation and lay the foundation for its successful realization.
Keywords: Small Business; Digital Transformation; Data-Driven Decision Making; POS Systems; Cloud Storage